Generation of Nonmosaic, Two-Pore Channel 2 Biallelic Knockout Pigs in One Generation by CRISPR-Cas9 Microinjection Before Oocyte Insemination - Navarro-Serna, Sergio (2022)
Abstract Studies of knockout (KO) mice with defects in the endolysosomal two-pore channels (TPCs) have shown TPCs to be involved in pathophysiological processes, including heart and muscle function, metabolism, immunity, cancer, and viral infection. With the objective of studying TPC2’s pathophysiological roles for the first time in a large, more humanlike animal model, TPC2 KO pigs were produced using CRISPR-Cas9. A major problem using CRISPR-Cas9 to edit embryos is mosaicism; thus, we studied for the first time the effect of microinjection timing on mosaicism. Mosaicism was greatly reduced when in vitro produced embryos were microinjected be- fore insemination, and surgical embryo transfer (ET) was performed using such embryos. All TPC2 KO fetuses and piglets born following ET (i.e., F0 generation) were nonmosaic biallelic KOs. The generation of nonmosaic animals greatly facilitates germ line transmission of the mutation, thereby aiding the rapid and efficient generation of KO animal lines for medical research and agriculture.